Objective and Subjective Burden in People with Mental Illness: Empirical Evidence - Cruz Ortiz, Maribel; Pérez Rodríguez, María del Carmen; Villegas Moreno, Elida Lisbeth; Flores Robaina, Noelia; Hernández Ibarra, Eduardo; Reyes Laris, Pedro (Pensando Psicología, 2013)
Diverse studies mention the consequences generated by providing special care to patients, particularly when associated with mental illness. The objective of this research was to analyze scientific studies published between 2003 and 2010 on the burden suffered by caregivers of patients with mental illnesses. A systematic review was made of literature found in open access databases (Scielo, Pubmed, Lilacs). The results suggest that, regardless of gender and marital status, when using strategies such as coping mechanisms and social support, younger patients have a greater impact on the burden felt by their caregivers than their older counterparts. This burden varies over time and is influenced by the type of symptomatology experienced by the patient and it is improbable that there will be improvement without some type of intervention.